Study the Physical Properties of Medium Density Fiberboard Utilized by Hybrid Mixture of Efb Fiber and Kenaf Fiber - Redwan, Amamer; Badri, Khairiah Haji; Bahrum, Azizah (Al-Nahrain Journal of Science, 2019)
In this study, a new hybrid medium density fiberboard was formulated by utilizing a fiber mixture composing of 50:50 empty fruit bunch and kenaf fiber coupled with palm-based pre-Polyurethane functioning as a binder. Kenaf as well as Empty fruit bunch fibers had a size range of 300 to 500 μm. Aluminum trihydroxide was used as the fire retardant at loading percentage of 0, 5, 10, and 15 wt% of total mass of the matrix. Water absorption property for hybrid-MDF showed a different trend in water absorption capability and this can be correlated to the strong dependence on the interface adhesion between fiber and the polymer matrix. The water absorption decreased as the loading level of Aluminum trihydroxide increased (6.5 – 2.3%) due to that fibers are held to each other through the interfacial bonding in the presence of Aluminum trihydroxide.